Multi-component doped ultralow-loss optical fiber and preparation method thereof

Through the multi-component doped fiber structure, the difficulties of existing optical fibers in transmission loss optimization, mode field diameter expansion, environmental adaptability and mechanical strength are solved, and ultra-low loss, wide band support and high mechanical strength are achieved, which are suitable for the needs of modern optical communication systems.

CN119644500APending Publication Date: 2025-03-18JIANGSU HENGTONG OPTICAL FIBER TECH +3
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411861859.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Existing optical fibers have difficulties in transmission loss optimization, mode field diameter expansion, environmental adaptability and mechanical strength, and are difficult to meet the needs of modern optical communication systems for ultra-low loss, wide band support, mechanical strength and environmental adaptability.

Method used

A multi-component doped optical fiber structure is adopted, including a core layer, a sub-core layer, a gradient control layer, a nonlinear functional layer, an absorption layer, an isolation layer, a thermal stabilization layer, a support layer, a transition protection layer and an outer cladding layer. By doping different elements and optimizing the refractive index difference of each layer, ultra-low loss, mode field expansion and environmental adaptability are achieved.

Benefits of technology

It realizes the transmission loss in the 1550nm band to 0.145dB/km, supports S+C+L band communication of 1300-1625nm, enhances the mechanical strength and environmental adaptability of the optical fiber, and is suitable for long-distance communication and harsh environment applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119644500A_ABST
    Figure CN119644500A_ABST
Patent Text Reader

Abstract

The invention discloses a multi-component doped ultralow-loss optical fiber and a preparation method thereof. The optical fiber comprises a fiber core layer, a secondary core layer, a gradient control layer, a nonlinear functional layer, an absorption layer, an isolation layer, a thermal stability layer, a supporting layer, a transition protection layer and an outer cladding which are arranged from inside to outside. According to the optical fiber, the 1550nm wave band attenuation is reduced to 0.145 dB / km, and ultralow loss is realized; the diameter of a mode field reaches 11-16 [mu] m, and mode interference is effectively reduced; the optical fiber supports communication of S + C + L wave bands of 1300-1625 nm, when 100 circles of looping with the radius of 60 mm are carried out, the maximum additional attenuation at the position of 1550 nm does not exceed 0.01 dB, and the optical fiber is suitable for long-distance communication; the environment adaptability of the optical fiber is high, the stability of the optical fiber in high-temperature, high-humidity and strong-mechanical-stress environments is enhanced by arranging the thermal stability layer and the supporting layer and combining the zirconium doping design of the outer cladding, and the optical fiber is particularly suitable for submarine optical cables and high-reliability backbone networks.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of optical communication, and in particular relates to a multi-component doped ultra-low loss optical fiber and a preparation method thereof. Background Art

[0002] Ultra-low loss optical fiber is the core transmission medium of optical communication systems and plays an irreplaceable role in long-distance, high-capacity optical fiber communications. With the growing demand for modern optical networks, especially the construction of submarine optical cables and backbone networks, lower loss, stronger environmental adaptability and wider transmission wavelength range are required:

[0003] 1. Ultra-low loss: The transmission loss in the 1550nm band must be less than 0.145dB / km;

[0004] 2. Large mode field diameter: A mode field diameter of 11-16 μm is required to reduce mode interference;

[0005] 3. Wide-band support: The optical fiber is required to adapt to the S+C+L band (1300-1625nm);

[0006] 4. Mechanical strength and environmental adaptability: After aging at 85°C and 85% relative humidity, the 50% dynamic tensile strength value of Weibull distribution is ≥4500Mpa for more than 20 consecutive groups; after aging at 85°C and 85% relative humidity, the Weibull slope is >100, and it can work stably for a long time under high mechanical stress and complex climate environment.

[0007] However, due to the limitations of material purity and doping technology, it is difficult to optimize the transmission loss of current optical fibers. It is difficult to further reduce the transmission loss to below 0.15dB / km. Although doping with GeO2 (commonly used in traditional optical fibers) can increase the refractive index, too high a value will increase Rayleigh scattering. - Ion absorption and Rayleigh scattering are still the main sources of loss. Secondly, the mode field diameter of the optical fiber is limited and cannot meet the requirement of 11-16μm. In addition, the interference in high-order modes is significant, which can easily lead to reduced signal purity, especially in long-distance transmission. Furthermore, the current environmental adaptability of optical fibers is poor. Under conditions of high temperature, high humidity, and strong mechanical stress, the mechanical strength and transmission performance of optical fibers are significantly reduced, making it difficult to meet the requirements of harsh environments such as submarine optical cables. The outer cladding of the optical fiber is insufficient in terms of bending resistance and tensile strength, and it is easy for the performance of the optical fiber to deteriorate due to long-term mechanical stress. Summary of the invention

[0008] In order to solve the technical problems existing in the prior art, the object of the present invention is to provide a multi-component doped ultra-low loss optical fiber and a preparation method thereof.

[0009] In order to achieve the above purpose and the above technical effect, the technical solution adopted by the present invention is:

[0010] A multi-component doped ultra-low loss optical fiber comprises a core layer, a sub-core layer, a gradient control layer, a nonlinear functional layer, an absorption layer, an isolation layer, a thermal stability layer, a support layer, a transition protection layer and an outer cladding layer which are sequentially arranged from the inside to the outside.

[0011] Furthermore, the radius R1 of the core layer is 5.8±0.3μm, the relative refractive index difference Δ1 is 0.3±0.03%, the doping concentration of the alkali metal in the core layer is 0.1-0.4mol%, and the doping concentration of the phosphorus element is 0.1-0.2mol%; the radius R2 of the sub-core layer is 9.5±0.5μm, the relative refractive index difference Δ2 is -0.15±0.02%, and the doping concentration of the F element in the sub-core layer is 0.5-1mol%.

[0012] Furthermore, the radius R3 of the gradient control layer is 14.5±0.7 μm, the relative refractive index difference Δ3 is -0.05±0.03%, and the doping concentration of the F element in the gradient control layer is 0.1-0.3 mol%.

[0013] Furthermore, the radius R4 of the nonlinear functional layer is 20±0.7 μm, the relative refractive index difference Δ4 is ​​0.2±0.03%, the doping concentration of GeO2 in the nonlinear functional layer is 1.5-2 mol%, and the doping concentration of P2O5 is 0.4-0.5 mol%.

[0014] Furthermore, the radius R5 of the absorption layer is 25±1 μm, the relative refractive index difference Δ5 is -0.1±0.02%, the doping concentration of the Pr element in the absorption layer is 40-50 ppm, and the doping concentration of the Dy element is 50-60 ppm.

[0015] Furthermore, the radius R6 of the isolation layer is 29±1 μm, the relative refractive index difference Δ6 is -0.15±0.03%, and the doping concentration of the F element in the isolation layer is 1.5-1.8 mol%.

[0016] Furthermore, the radius R7 of the thermal stability layer is 35±1 μm, the relative refractive index difference Δ7 is 0.1±0.03%, the doping concentration of GeO2 in the thermal stability layer is 0.9-1.1 mol%, and the doping concentration of Al2O3 is 0.8-1 mol%.

[0017] Furthermore, the radius R8 of the support layer is 39±1 μm, the relative refractive index difference Δ8 is 0.05±0.02%, the doping concentration of GeO2 in the support layer is 1-1.5 mol%, and the doping concentration of P2O5 is 0.8-1 mol%.

[0018] Furthermore, the radius R9 of the transition protection layer is 49.5±1 μm, and the relative refractive index difference Δ9 is 0%; the radius R10 of the outer cladding is 61.5±1 μm, and the relative refractive index difference Δ10 is 0.05±0.02%, and the doping concentration of ZrO2 in the outer cladding is 1-2 mol%.

[0019] The present invention also discloses a method for preparing a multi-component doped ultra-low loss optical fiber, wherein the ultra-low loss optical fiber is prepared by using a PCVD or MCVD process;

[0020] The steps of preparing the ultra-low loss optical fiber by PCVD process include:

[0021] 1) Select a pure silicon liner or a liner doped with metal ions, and introduce inert gas into the liner to reduce the hydroxyl content in the liner;

[0022] 2) Install the pure silicon liner or the liner doped with metal ions on the deposition machine of the PCVD process to perform ultra-low loss core rod deposition:

[0023] 21) Deposition of outer cladding: introducing reactants containing Zr, Si and F into the liner tube, with high-purity O2 as the carrier gas, the relative refractive index difference Δ10 of the outer cladding reaching 0.05±0.02%, and the doping concentration of ZrO2 in the outer cladding being 1-2 mol%;

[0024] 22) Deposition of transition protection layer: reactants containing Si and F are introduced into the outer cladding, and the carrier gas is high-purity O2;

[0025] 23) Deposition of support layer: introducing reactants containing Ge, P, Si, and F into the transition protective layer, with high-purity O2 as the carrier gas, so that the relative refractive index difference Δ8 of the support layer is 0.05±0.02%, the doping concentration of GeO2 in the support layer is 1-1.5 mol%, and the doping concentration of P2O5 is 0.8-1 mol%;

[0026] 24) Deposition of thermal stability layer: introducing reactants containing Ge, Al, Si and F into the support layer, with high-purity O2 as the carrier gas, so that the relative refractive index difference Δ7 of the thermal stability layer is 0.1±0.03%, the doping concentration of GeO2 in the thermal stability layer is 0.9-1.1 mol%, and the doping concentration of Al2O3 is 0.8-1 mol%;

[0027] 25) Deposition of isolation layer: introducing reactants containing Si and F into the thermal stability layer, with high-purity O2 as the carrier gas, so that the relative refractive index difference Δ6 of the isolation layer reaches -0.15±0.03%, and the doping concentration of F element in the isolation layer is 1.5-1.8 mol%;

[0028] 26) Deposition of the absorption layer: introducing reactants containing Pr, Dy, Si, and F into the isolation layer, with high-purity O2 as the carrier gas, so that the relative refractive index difference Δ5 of the absorption layer reaches -0.1±0.02%, the doping concentration of the Pr element in the absorption layer is 40-50ppm, and the doping concentration of the Dy element is 50-60ppm;

[0029] 27) Deposition of nonlinear functional layer: introducing reactants containing Ge, P, Si and F into the absorption layer, with high-purity O2 as the carrier gas, so that the relative refractive index difference Δ4 of the nonlinear functional layer reaches 0.2±0.03%, and the doping concentration of GeO2 in the nonlinear functional layer is 1.5-2mol%, and the doping concentration of P2O5 is 0.4-0.5mol%;

[0030] 28) Deposition of gradient control layer: introducing reactants containing Si and F into the nonlinear functional layer, with high-purity O2 as the carrier gas, so that the relative refractive index difference Δ3 of the gradient control layer reaches -0.05±0.03%, and the doping concentration of F element in the gradient control layer is 0.1-0.3 mol%;

[0031] 29) Deposition of the sub-core layer: introducing reactants containing Si and F into the gradient control layer, with high-purity O2 as the carrier gas, so that the relative refractive index difference Δ2 of the sub-core layer reaches -0.15±0.02%, and the doping concentration of the F element in the sub-core layer is 0.5-1 mol%;

[0032] 30) Deposition of the core layer: introducing reactants containing alkali metals, P, Si, and F into the first transition layer, with high-purity O2 as the carrier gas, so that the relative refractive index difference Δ1 of the core layer reaches 0.3±0.03%, the doping concentration of the alkali metal in the core layer is 0.1-0.4 mol%, and the doping concentration of the P element is 0.1-0.2 mol%;

[0033] 3) After the deposition is completed, caps should be placed on both ends of the liner before the rod is moved to prevent air from entering and ensure the ultra-low attenuation performance of the core rod. The tube should be quickly moved and installed behind the melting and shrinking bed, and purged with high-purity O2 to reduce the hydroxyl content in the liner.

[0034] 4) Melt and shrink the liner tube to a solid core rod at a melting temperature of 1500-2200°C. During the melting process, high-purity O2 is introduced at a flow rate of 1500-2500sccm. The internal pressure of the melting tube is controlled at 5-15Pa.

[0035] 5) According to the design size of the core rod, match the corresponding sleeve so that the optical fiber meets the design thickness requirements of R1~R10.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] 1) The core layer uses pure silicon core doped with alkali metals and P elements. Doping with alkali metals can reduce the OH in the material. - Ion content, reducing water peak absorption loss. P doping can increase the refractive index and optimize material stress distribution, inhibit Rayleigh scattering, reduce basic loss, and help reduce the attenuation in the 1550nm band to 0.145dB / km, while enhancing the mechanical strength of the optical fiber.

[0038] 2) The sub-core layer adopts a negative refractive index design and is doped with fluorine (F: 0.5-1mol%) for mode field expansion and mode confinement;

[0039] 3) F is doped in the gradient transition layer to achieve mode field gradient transition, enhance mode field stability, and reduce the effects of Rayleigh scattering and high-order mode coupling on transmission loss;

[0040] 4) Doping GeO2 and P2O5 in the nonlinear functional layer is used to optimize the mode field distribution and suppress the nonlinear effect;

[0041] 5) The absorption layer is doped with rare earth (Pr, Dy) to absorb high-order mode light and improve signal purity;

[0042] 6) The isolation layer adopts a negative refractive index design to suppress mode leakage and ensure high purity of mode transmission;

[0043] 7) Doping GeO2 and Al2O3 in the thermal stability layer can enhance the stability of the optical fiber under high temperature and high humidity conditions;

[0044] 8) GeO2 and P2O5 are doped in the support layer to provide mechanical support for the optical fiber, enhance its bending resistance, and prevent the influence of external mechanical stress on the optical fiber performance;

[0045] 9) Doping ZrO2 in the outer cladding can significantly enhance the mechanical properties of the outer cladding, improve the tensile strength and bending resistance;

[0046] 10) The present invention reduces the 1550nm transmission loss to 0.145dB / km through alkali metal doping and rare earth doping design, achieving ultra-low loss;

[0047] 11) The optical fiber of the present invention supports S+C+L band communication of 1300-1625nm. When looped with a radius of 60mm for 100 turns, the maximum additional attenuation at 1550nm does not exceed 0.01dB. The 50% dynamic tensile strength value of the Weibull distribution after aging at 85°C and 85% relative humidity is ≥4500Mpa. The Weibull slope after aging at 85°C and 85% relative humidity for more than 20 consecutive groups is >100, and it is suitable for long-distance communication.

[0048] 12) The optical fiber of the present invention has strong environmental adaptability. By providing a thermal stability layer and a support layer and combining the zirconium doping design of the outer cladding, the stability of the optical fiber in high temperature, high humidity and strong mechanical stress environments is enhanced, and it is particularly suitable for submarine optical cables and high-reliability backbone networks. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 It is a schematic diagram of the refractive index profile of the present invention. DETAILED DESCRIPTION

[0050] The present invention is described in detail below so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more definite definition of the protection scope of the present invention.

[0051] A brief summary of one or more aspects is given below to provide a basic understanding of these aspects. This summary is not an exhaustive overview of all conceived aspects, and is neither intended to identify the key or critical elements of all aspects nor to define the scope of any or all aspects. Its only purpose is to give some concepts of one or more aspects in a simplified form as a prelude to a more detailed description that will be given later.

[0052] like Figure 1 As shown, the present invention discloses a multi-component doped ultra-low loss optical fiber, which aims to significantly reduce transmission loss, optimize mode field distribution, improve optical fiber strength, and enhance the environmental adaptability of optical fiber.

[0053] The ultra-low loss optical fiber mainly includes a core layer, a sub-core layer, a gradient control layer, a nonlinear functional layer, an absorption layer, an isolation layer, a thermal stability layer, a support layer, a transition protection layer and an outer cladding layer which are arranged in sequence from the inside to the outside.

[0054] The parameters and functions of the core layer are:

[0055] The radius R1 is 5.8 ± 0.3 μm;

[0056] The relative refractive index difference Δ1 is 0.3±0.03%;

[0057] Doping elements and concentrations are: alkali metal (K or Na): 0.1-0.4 mol%; P: 0.1-0.2 mol%;

[0058] Function: The relative refractive index difference is maintained within a reasonable range, which meets the requirements of single-mode optical fiber transmission mode and can ensure mode field constraint and single-mode stability;

[0059] Loss characteristics: The core layer uses pure silicon core doped with alkali metals and P elements. Doping with alkali metals can reduce the OH in the material. -Ion content, reducing water peak absorption loss, by doping P can increase the refractive index and optimize the material stress distribution, inhibit Rayleigh scattering, reduce basic loss, and enhance the mechanical strength of the optical fiber;

[0060] Mode field diameter optimization: By optimizing the refractive index distribution and doping concentration, the mode field diameter range is adjusted to 11-16μm to meet the needs of long-distance transmission.

[0061] The parameters and functions of the sub-core layer are:

[0062] Radius R2: 9.5 ± 0.5 μm;

[0063] The relative refractive index difference Δ2 is -0.15±0.02% (negative refractive index);

[0064] The doping elements and concentrations are: F: 0.5-1mol%, reducing the refractive index and optimizing the mode field expansion;

[0065] Function: Used for mode field expansion and mode constraint. Negative refractive index design optimizes mode field distribution, reduces mode interference, and lays the foundation for efficient single-mode transmission.

[0066] The parameters and functions of the gradient control layer are:

[0067] Radius R3: 14.5 ± 0.7 μm;

[0068] The relative refractive index difference Δ3 is -0.05±0.03% (negative refractive index);

[0069] The doping elements and concentrations are: F: 0.1-0.3 mol%, reducing mode coupling;

[0070] Function: Mode field gradient transition, enhancing mode field stability, reducing the impact of Rayleigh scattering and high-order mode coupling on transmission loss.

[0071] The parameters and functions of the nonlinear functional layer are:

[0072] Radius R4: 20 ± 0.7 μm;

[0073] The relative refractive index difference Δ4 is ​​0.2±0.03% (positive value);

[0074] The doping elements and concentrations are: GeO2: 1.5-2mol%, providing nonlinear optical response; P2O5: 0.4-0.5mol%, further enhancing nonlinear performance;

[0075] Function: Optimize mode field distribution, enhance optical fiber nonlinear response capability, and reduce the adverse effects of nonlinear effects.

[0076] The parameters and functions of the absorbing layer are:

[0077] Radius R5: 25 ± 1 μm;

[0078] The relative refractive index difference Δ5 is -0.1±0.02%;

[0079] The doping elements and concentrations are: Pr element: 40-50ppm, absorbing high-order mode light; Dy element: 50-60ppm, further enhancing the stray light absorption effect;

[0080] Function: Absorb stray light and high-order mode light, improve signal purity, and provide higher stability for main mode signal transmission.

[0081] The parameters and functions of the isolation layer are:

[0082] Radius R6: 29 ± 1 μm;

[0083] The relative refractive index difference Δ6 is -0.15±0.03%;

[0084] Doping elements and concentration: F: 1.5-1.8 mol%, further reducing the refractive index and enhancing the isolation performance;

[0085] Function: Block mode leakage, ensure high purity of fiber mode transmission, and provide additional mode field confinement capability.

[0086] The parameters and functions of the thermal stabilization layer are:

[0087] Radius R7: 35 ± 1 μm;

[0088] The relative refractive index difference Δ7 is 0.1±0.03%;

[0089] Doping elements and concentrations: GeO2: 0.9-1.1mol%, to enhance thermal stability; Al2O3: 0.8-1mol%, to improve stress resistance;

[0090] Function: Improve the performance stability of optical fiber in high temperature and high humidity environments and reduce the loss changes caused by thermal expansion.

[0091] The parameters and functions of the support layer are:

[0092] Radius R8: 39 ± 1 μm;

[0093] The relative refractive index difference Δ8 is 0.05±0.02%;

[0094] Doping elements and concentrations are: GeO2: 1-1.5mol%, to enhance mechanical properties; P2O5: 0.8-1mol%, to optimize stress distribution;

[0095] Function: Provide mechanical support for optical fiber, enhance its bending resistance, and prevent external mechanical stress from affecting its performance.

[0096] The parameters and functions of the transition protection layer are:

[0097] Radius R9: 49.5 ± 1 μm;

[0098] The relative refractive index difference Δ9 is 0%;

[0099] Doping elements and concentration: pure SiO2;

[0100] Function: Provide mode field transition, environmental isolation and basic protection to prevent external environmental factors (such as moisture and pollution) from affecting the optical fiber.

[0101] The parameters and functions of the outer layer are:

[0102] Radius R10: 61.5 ± 1 μm;

[0103] The relative refractive index difference Δ10 is 0.05±0.02%;

[0104] Doping elements and concentration: ZrO2: 1-2mol%, to enhance the mechanical properties of the outer cladding, improve tensile strength and bending resistance;

[0105] Function: Provide high-strength mechanical protection, adapt to complex environments (such as the seabed and high pressure), improve the tensile and bending resistance of optical fibers, and ensure long-term stable operation.

[0106] The above 10-layer structure is functionally progressive, covering multiple aspects of optical fiber transmission performance optimization. The doping concentration and refractive index difference of each layer are precisely optimized to ensure mode field expansion, mode constraint and optical fiber stability. The refractive index gradient distribution of each layer ensures a smooth transition of mode field diameter and high-order mode coupling, reduces Rayleigh scattering and mode field leakage losses, and meets the needs of modern optical communication systems for high-speed, large-capacity and long-distance transmission. It is suitable for long-distance ultra-low-loss optical communications and applications in harsh environments (such as submarine optical cables).

[0107] The invention also discloses a method for preparing a multi-component doped ultra-low loss optical fiber. The ultra-low loss optical fiber is prepared by adopting a PCVD or MCVD process.

[0108] The steps of preparing the ultra-low loss optical fiber using the PCVD process include:

[0109] 1) Use pure silicon liner or liner doped with metal ions, after pickling, place on a drying rack for drying, pass inert gas (Ar) into the tube, the temperature is 50-70°C, purge for 12-24h, this step mainly reduces the hydroxyl content in the liner. The metal ions are one or more combinations of metal ions such as Na, Pr, Zr, Dy, etc.;

[0110] 2) Install the purged pure silicon liner or the liner doped with metal ions on the deposition machine of the PCVD process to perform ultra-low loss core rod deposition:

[0111] 21) Deposition of outer cladding: introducing reactants containing Zr, Si and F into the liner tube, and using high-purity O2 as carrier gas; the relative refractive index difference Δ10 of the outer cladding reaches 0.05±0.02%, and the doping concentration of ZrO2 in the outer cladding is 1-2 mol%;

[0112] 22) Deposition of transition protection layer: reactants containing Si and F are introduced into the outer cladding, and the carrier gas is high-purity O2;

[0113] 23) Deposition of support layer: introducing reactants containing Ge, P, Si, and F into the transition protective layer, with high-purity O2 as the carrier gas, so that the relative refractive index difference Δ8 of the support layer is 0.05±0.02%, the doping concentration of GeO2 in the support layer is 1-1.5 mol%, and the doping concentration of P2O5 is 0.8-1 mol%;

[0114] 24) Deposition of thermal stability layer: introducing reactants containing Ge, Al, Si and F into the support layer, with high-purity O2 as the carrier gas, so that the relative refractive index difference Δ7 of the thermal stability layer is 0.1±0.03%, the doping concentration of GeO2 in the thermal stability layer is 0.9-1.1 mol%, and the doping concentration of Al2O3 is 0.8-1 mol%;

[0115] 25) Deposition of isolation layer: introducing reactants containing Si and F into the thermal stability layer, with high-purity O2 as the carrier gas, so that the relative refractive index difference Δ6 of the isolation layer reaches -0.15±0.03%, and the doping concentration of F element in the isolation layer is 1.5-1.8 mol%;

[0116] 26) Deposition of the absorption layer: introducing reactants containing Pr, Dy, Si, and F into the isolation layer, with high-purity O2 as the carrier gas, so that the relative refractive index difference Δ5 of the absorption layer reaches -0.1±0.02%, the doping concentration of the Pr element in the absorption layer is 40-50ppm, and the doping concentration of the Dy element is 50-60ppm;

[0117] 27) Deposition of nonlinear functional layer: introducing reactants containing Ge, P, Si and F into the absorption layer, with high-purity O2 as the carrier gas, so that the relative refractive index difference Δ4 of the nonlinear functional layer reaches 0.2±0.03%, and the doping concentration of GeO2 in the nonlinear functional layer is 1.5-2mol%, and the doping concentration of P2O5 is 0.4-0.5mol%;

[0118] 28) Deposition of gradient control layer: introducing reactants containing Si and F into the nonlinear functional layer, with high-purity O2 as the carrier gas, so that the relative refractive index difference Δ3 of the gradient control layer reaches -0.05±0.03%, and the doping concentration of F element in the gradient control layer is 0.1-0.3 mol%;

[0119] 29) Deposition of the sub-core layer: introducing reactants containing Si and F into the gradient control layer, with high-purity O2 as the carrier gas, so that the relative refractive index difference Δ2 of the sub-core layer reaches -0.15±0.02%, and the doping concentration of the F element in the sub-core layer is 0.5-1 mol%;

[0120] 30) Deposition of the core layer: introducing reactants containing alkali metal (K or Na), P, Si, and F into the first transition layer, with high-purity O2 as the carrier gas, so that the relative refractive index difference Δ1 of the core layer reaches 0.3±0.03%, the doping concentration of the alkali metal in the core layer is 0.1-0.4 mol%, and the doping concentration of the phosphorus element is 0.1-0.2 mol%;

[0121] 3) After the liner tube is deposited, caps need to be placed on both ends of the liner tube before the rod is moved to prevent air from entering and ensure the ultra-low attenuation performance of the core rod. After the tube is quickly moved and installed on the melting bed, it needs to be purged with high-purity O2 to reduce the hydroxyl content in the liner tube during the installation of the deposition tube. The O2 flow rate is 100-2500sccm and the purging time is 3-10min.

[0122] 4) The deposited liner is melted and shrunk into a solid core rod at a melting temperature of 1500-2200°C. During the melting process, high-purity O2 is introduced at a flow rate of 1500-2500sccm. The internal pressure of the melting tube is controlled at 5-15Pa.

[0123] 5) According to the design size of the core rod, match the corresponding sleeve so that the optical fiber meets the design thickness requirements of R1~R10.

[0124] Parts or structures not specifically described in the present invention may adopt existing technologies or existing products and will not be described in detail here.

[0125] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A multi-component doped ultra-low loss optical fiber, characterized in that: It includes a core layer, a sub-core layer, a gradient control layer, a nonlinear functional layer, an absorption layer, an isolation layer, a thermal stability layer, a support layer, a transition protection layer and an outer cladding layer which are arranged in sequence from the inside to the outside.

2. The multi-component doped ultra-low loss optical fiber according to claim 1, characterized in that: The radius R1 of the core layer is 5.8±0.3μm, the relative refractive index difference Δ1 is 0.3±0.03%, the doping concentration of alkali metal in the core layer is 0.1-0.4mol%, and the doping concentration of phosphorus is 0.1-0.2mol%; the radius R2 of the sub-core layer is 9.5±0.5μm, the relative refractive index difference Δ2 is -0.15±0.02%, and the doping concentration of F element in the sub-core layer is 0.5-1mol%.

3. The multi-component doped ultra-low loss optical fiber according to claim 1, characterized in that: The radius R3 of the gradient control layer is 14.5±0.7 μm, the relative refractive index difference Δ3 is -0.05±0.03%, and the doping concentration of the F element in the gradient control layer is 0.1-0.3 mol%.

4. The multi-component doped ultra-low loss optical fiber according to claim 1, characterized in that: The radius R4 of the nonlinear functional layer is 20±0.7 μm, the relative refractive index difference Δ4 is ​​0.2±0.03%, the doping concentration of GeO2 in the nonlinear functional layer is 1.5-2 mol%, and the doping concentration of P2O5 is 0.4-0.5 mol%.

5. The multi-component doped ultra-low loss optical fiber according to claim 1, characterized in that: The radius R5 of the absorption layer is 25±1 μm, the relative refractive index difference Δ5 is -0.1±0.02%, the doping concentration of the Pr element in the absorption layer is 40-50 ppm, and the doping concentration of the Dy element is 50-60 ppm.

6. The multi-component doped ultra-low loss optical fiber according to claim 1, characterized in that: The radius R6 of the isolation layer is 29±1 μm, the relative refractive index difference Δ6 is -0.15±0.03%, and the doping concentration of the F element in the isolation layer is 1.5-1.8 mol%.

7. The multi-component doped ultra-low loss optical fiber according to claim 1, characterized in that: The radius R7 of the thermal stability layer is 35±1 μm, the relative refractive index difference Δ7 is 0.1±0.03%, the doping concentration of GeO2 in the thermal stability layer is 0.9-1.1 mol%, and the doping concentration of Al2O3 is 0.8-1 mol%.

8. The multi-component doped ultra-low loss optical fiber according to claim 1, characterized in that: The radius R8 of the support layer is 39±1 μm, the relative refractive index difference Δ8 is 0.05±0.02%, the doping concentration of GeO2 in the support layer is 1-1.5 mol%, and the doping concentration of P2O5 is 0.8-1 mol%.

9. The multi-component doped ultra-low loss optical fiber according to claim 1, characterized in that: The radius R9 of the transition protection layer is 49.5±1 μm, and the relative refractive index difference Δ9 is 0%; the radius R10 of the outer cladding is 61.5±1 μm, and the relative refractive index difference Δ10 is 0.05±0.02%, and the doping concentration of ZrO2 in the outer cladding is 1-2 mol%.

10. A method for preparing a multi-component doped ultra-low loss optical fiber, characterized in that: The ultra-low loss optical fiber is prepared by PCVD or MCVD process; The steps of preparing the ultra-low loss optical fiber by PCVD process include: 1) Select a pure silicon liner or a liner doped with metal ions, and introduce an inert gas into the liner to reduce the hydroxyl content in the liner; 2) Install the pure silicon liner or the liner doped with metal ions on the deposition machine of the PCVD process to perform ultra-low loss core rod deposition: 21) Deposition of outer cladding: introducing reactants containing Zr, Si and F into the liner tube, with high-purity O2 as the carrier gas, the relative refractive index difference Δ10 of the outer cladding reaching 0.05±0.02%, and the doping concentration of ZrO2 in the outer cladding being 1-2 mol%; 22) Deposition of transition protection layer: reactants containing Si and F are introduced into the outer cladding, and the carrier gas is high-purity O2; 23) Deposition of support layer: introducing reactants containing Ge, P, Si, and F into the transition protective layer, with high-purity O2 as the carrier gas, so that the relative refractive index difference Δ8 of the support layer is 0.05±0.02%, the doping concentration of GeO2 in the support layer is 1-1.5 mol%, and the doping concentration of P2O5 is 0.8-1 mol%; 24) Deposition of thermal stability layer: introducing reactants containing Ge, Al, Si and F into the support layer, with high-purity O2 as the carrier gas, so that the relative refractive index difference Δ7 of the thermal stability layer is 0.1±0.03%, the doping concentration of GeO2 in the thermal stability layer is 0.9-1.1 mol%, and the doping concentration of Al2O3 is 0.8-1 mol%; 25) Deposition of isolation layer: introducing reactants containing Si and F into the thermal stability layer, with high-purity O2 as the carrier gas, so that the relative refractive index difference Δ6 of the isolation layer reaches -0.15±0.03%, and the doping concentration of F element in the isolation layer is 1.5-1.8 mol%; 26) Deposition of the absorption layer: introducing reactants containing Pr, Dy, Si, and F into the isolation layer, with high-purity O2 as the carrier gas, so that the relative refractive index difference Δ5 of the absorption layer reaches -0.1±0.02%, the doping concentration of the Pr element in the absorption layer is 40-50ppm, and the doping concentration of the Dy element is 50-60ppm; 27) Deposition of nonlinear functional layer: introducing reactants containing Ge, P, Si and F into the absorption layer, with high-purity O2 as the carrier gas, so that the relative refractive index difference Δ4 of the nonlinear functional layer reaches 0.2±0.03%, and the doping concentration of GeO2 in the nonlinear functional layer is 1.5-2mol%, and the doping concentration of P2O5 is 0.4-0.5mol%; 28) Deposition of gradient control layer: introducing reactants containing Si and F into the nonlinear functional layer, with high-purity O2 as the carrier gas, so that the relative refractive index difference Δ3 of the gradient control layer reaches -0.05±0.03%, and the doping concentration of F element in the gradient control layer is 0.1-0.3 mol%; 29) Deposition of the sub-core layer: introducing reactants containing Si and F into the gradient control layer, with high-purity O2 as the carrier gas, so that the relative refractive index difference Δ2 of the sub-core layer reaches -0.15±0.02%, and the doping concentration of the F element in the sub-core layer is 0.5-1 mol%; 30) Deposition of the core layer: introducing reactants containing alkali metals, P, Si, and F into the first transition layer, with high-purity O2 as the carrier gas, so that the relative refractive index difference Δ1 of the core layer reaches 0.3±0.03%, the doping concentration of the alkali metal in the core layer is 0.1-0.4 mol%, and the doping concentration of the P element is 0.1-0.2 mol%; 3) After the deposition is completed, caps should be placed on both ends of the liner before the rod is moved to prevent air from entering and ensure the ultra-low attenuation performance of the core rod. The tube should be quickly moved and installed behind the melting and shrinking bed, and purged with high-purity O2 to reduce the hydroxyl content in the liner. 4) Melt and shrink the liner tube to a solid core rod at a melting temperature of 1500-2200°C. During the melting process, high-purity O2 is introduced at a flow rate of 1500-2500sccm. The internal pressure of the melting tube is controlled at 5-15Pa. 5) According to the design size of the core rod, match the corresponding sleeve so that the optical fiber meets the design thickness requirements of R1~R10.